Portable flexible probe for detecting blood supply status in clinical surgery - Xia, Jie; Pan, Jiadong; Yan, Ruijian; Zhang, Fan; Zhang, Luxi; Feng, Gang; Luo, Jack; Dong, Shurong; Wang, Yueming (Frontiers in Physics, 2022)
In the medical field, it is Important to monitor and evaluate the blood supply status of organs and tissues during the clinical surgery. However, this largely depends on the surgeon's experience and naked eye, which is easy to misjudge due to the interference of blood stains or other factors. A portable and flexible PPG detection probe is developed in this paper. And a new evaluation methodology of blood supply status is proposed based on this probe. Three typical indicators based on photoplethysmographic (PPG) is proposed to comprehensively evaluate the blood supply status, which are the blood oxygen saturation and its pulsation, differential characteristics of different lights, and time-frequency energy spectral characteristic. The probe and its evaluation methodology are verified using the brain of rats as a model.